PENGARUH LATIHAN SHOOTING MENGGUNAKAN METODE DRILL TERHADAP KETEPATAN SHOOTING DALAM PERMAINAN FUTSAL SISWA SEKOLAH DASAR - Firdaus, Aranda; Saputra, Yudha M Saputra M; Sudrazat, Adang (JURNAL ILMU KEOLAHRAGAAN, 2024)
Sport is a necessity for every human individual and is an important factor in efforts to improve physical condition. Futsal is a type of sport that is in great demand by the public, both among children, teenagers and adults. Where the goal is to score a goal towards the opponent's goal. Of course, this requires accuracy in shooting which can be honed through shooting practice. In this research, the method used is a quasi-experimental method with the research design used is One Group Pretest-posttest design. The population in this study were students in grades IV, V and VI at SDN Gunungsari. With an average age of 10-12 years there are 15 people. With data collection techniques, namely tests, and data analysis techniques using the t-test. The results displayed based on pretest, treatment and posttest activities show that shooting drill practice has an influence on students' shooting accuracy. Based on the results of data analysis, descriptions, testing of research results, and discussion, a conclusion can be drawn, namely that there is a significant influence of shooting drill training on shooting accuracy towards the goal of Gunungsari Elementary School students with tCount 9.012 > tTable 2.093 and a significance value of 0.000 < 0.05. In this way, there is an increase in shooting precision using the drill training method in futsal games